2020
DOI: 10.3390/catal10050502
|View full text |Cite
|
Sign up to set email alerts
|

Selective Production of Acetic Acid via Catalytic Fast Pyrolysis of Hexoses over Potassium Salts

Abstract: Glucose and fructose are widely available and renewable resources. They were used to prepare acetic acid (AA) under the catalysis of potassium acetate (KAc) by thermogravimetric analysis (TGA) and pyrolysis coupled with gas chromatography and mass spectrometry (Py-GC/MS). The TGA result showed that the KAc addition lowered the glucose’s thermal decomposition temperatures (about 30 °C for initial decomposition temperature and 40 °C for maximum mass loss rate temperature), implying its promotion of glucose’s dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…It can be assumed that under the technological conditions used—heating at a constant not very high temperature over a rather long period of time—glucose forms structures serving as a kind of framework. Glucose decomposition at heating was shown in [ 24 ] to start at 188 °C and reach maximum rate at 220 °C ( Table 1 in Ref. [ 24 ]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that under the technological conditions used—heating at a constant not very high temperature over a rather long period of time—glucose forms structures serving as a kind of framework. Glucose decomposition at heating was shown in [ 24 ] to start at 188 °C and reach maximum rate at 220 °C ( Table 1 in Ref. [ 24 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Glucose decomposition at heating was shown in [ 24 ] to start at 188 °C and reach maximum rate at 220 °C ( Table 1 in Ref. [ 24 ]). Moreover, this process can make some contribution to the curves shown in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of furans in pyrolysis products is associated with the carbohydrate in the feedstock. Kang and Zhang 100 showed that the pyrolysis product of pure glucose contains furans (most furfural and then 5‐HMF) by weight. The pyrolysis products of both FS and HTCFS contained furans (2‐methyl furan, 2,5‐dimethylfuran, and furfural).…”
Section: Resultsmentioning
confidence: 99%
“…These contaminations might have interfered the thermal decompositions of the carrageenan molecules. Some impurity elements were degraded earlier or close to the carrageenan decomposition temperature, such as glucose (Kang & Zhang, 2020;Quan, Gao, & Song, 2016). Meanwhile, others were decomposed at a higher temperature such as xylose, cellulose, and inorganic materials (ICF, 2011;Quan et al, 2016).…”
Section: Thermal Behaviourmentioning
confidence: 99%